The repeatability of digital force waveform during natural grasping with five digits. (May 2016) - Chen, Po-Tsun; Lin, Chien-Ju; Chieh, Hsiao-Feng; Kuo, Li-Chieh; Jou, I-Ming; Su, Fong-Chin
Highlights: A custom simulator is designed to record the digit force during each natural grasp. The digit force waveform during grasp is analyzed with respect to functional tasks. The repeatability of force waveform is related to force direction and task type. Thumb shows high force repeatability in radial during lift-hold-lower and in longitudinal during drinking. Abstract: Completing a functional grasping task with five digits requires the control of numerous degrees of freedom in digit force. However, the waveform repeatability of applied force during such tasks remains unknown. This study aimed to analyze the waveform repeatability of force in each digit during grasping. Twenty right-handed subjects were recruited. The digit forces in radial and longitudinal directions during lift-hold-lower and drinking tasks were obtained by a custom simulator with five force transducers and one accelerometer. The repeatability was higher for radial than longitudinal force during the lift-hold-lower task. The repeatability of longitudinal force was higher during the drinking task than lift-hold-lower task. The fair to good repeatability of force waveform implies the flexibility in the control of digit forces to compensate for various task demands and coordinate with other digits in counterbalancing instantaneous changes of the object's gravity force in motion.